1999
DOI: 10.1038/sj.ijo.0800842
|View full text |Cite
|
Sign up to set email alerts
|

A peptide leptin antagonist reduces food intake in rodents

Abstract: OBJECTIVE: The purpose of the present study was to investigate the continuing validity of the hypothesis that leptin is a physiologically important regulator of food intake, using the human leptin mutant R128Q leptin. DESIGN: In a cellular proliferation assay, based on BAF-3 cells transfected with the murine ObRb receptor, R128Q leptin was shown to be devoid of agonistic activity and to competitively inhibit the proliferative effects of leptin. To determine whether R128Q leptin was also an antagonist of leptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Earlier investigations revealed that under various experimental conditions leptin fragments exert biological effects both similar to and distinct from those of the native leptin molecule [7,[19][20][21][22][23][24][25]. Structure-activity studies revealed that two segments of the leptin molecule affect its in vivo and in vitro activities: (1) the N-terminal amino-acid sequence 22-115, which is essential for the biological and receptor-binding activities; and (2) the C-terminal sequence 116-166 possessing a loop structure, that enhances the activity of the N-terminal region.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier investigations revealed that under various experimental conditions leptin fragments exert biological effects both similar to and distinct from those of the native leptin molecule [7,[19][20][21][22][23][24][25]. Structure-activity studies revealed that two segments of the leptin molecule affect its in vivo and in vitro activities: (1) the N-terminal amino-acid sequence 22-115, which is essential for the biological and receptor-binding activities; and (2) the C-terminal sequence 116-166 possessing a loop structure, that enhances the activity of the N-terminal region.…”
Section: Discussionmentioning
confidence: 99%
“…Although these two mutations do not affect the binding to the mouse leptin receptor, they cause reduced biological activity [28]. Of particular, R149Q is unable to trigger intracellular signaling and behaves as a competitive inhibitor [29]. Although Arg-149 has not been predicted part of any of the three binding sites, this residue forms hydrogen bonds with the backbone of Pro-64 (in AB loop) and Val-134 (in helix E).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, leptin inhibition was shown to have several beneficial effects. A leptin peptide functioning as an antagonist mutant leptin reduced food intake when administered intracerebroventricularly [ 41 ]. Moreover, a leptin antagonist was shown to reverse hypertension induced by leptin central overexpression [ 42 ] and was proposed to be a novel therapeutic approach for the treatment of autoimmune diseases [ 43 ].…”
Section: Leptinmentioning
confidence: 99%